PENGARUH PENERAPAN SISTEM PERPAJAKAN DIGITAL DAN PEMAHAMAN WAJIB PAJAK TERHADAP KEPATUHAN PAJAK - Lina Rindi Antika; Eny Purwaningsih (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study was conducted to understand the relationship between the e-filing system, e-billing system, NIK matching on NPWP and taxpayer understanding of tax compliance. The Rohis Alumni Community of SMKN 13 Jakarta is the population of this study, and a sample of 52 respondents was selected using the Slovin formula. This study uses quantitative methods with normality, multicollinearity, heteroscedasticity, and linearity tests as classical assumption tests. For speculation testing using T test, F test, and coefficient of determination test. In this review, the information used is key information collected through distributing surveys to respondents. The research findings suggest that the e-filing system, e-billing, and matching NIK with NPWP have no impact on tax compliance. However, taxpayer understanding is proven to have a significant relationship with tax compliance. The research contribution is expected to provide additional information and insights regarding the importance of improving tax compliance. Suggestions for future research can use a wider population from a particular region or company, by adding or replacing variables, such as tax sanctions, e-fin, or e- registration